Peran Industri Kerajinan Karpet Dari Serat Pisang Abaka Dalam Meningkatkan Kesejahteraan Masyarakat - Fatimah Azahrah; Suryati Suryati; Muslimin Muslimin (Social Science and Contemporary Issues Journal, 2023)
This research discusses "The Role of the Carpet Craft Industry from Abaka Banana Fiber CV. Natural in Improving Community Welfare”. This research uses a qualitative approach by collecting data through observation, interviews and documentation methods. The objectives of this research are: 1) To determine the role of the carpet craft industry from CV banana abaca fiber. Natural in Improving Welfare, 2) To find out the results of the role of the carpet craft industry from CV banana abaca fiber. Natural. The subjects of this research were the head of personnel as a representative of the owner and employees who worked in the CV abaca banana fiber carpet craft industry. Natural City of Palembang. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results of this research show: 1) Carpet craft industry from abaca banana fiber CV. Natural in improving community welfare carries out a facilitative role to facilitate the community, an educational role to educate and provide education to the community, a representative role to negotiate and collaborate with outside parties and a technical skills role for workers so that they have skills that really require techniques in carrying out their duties. and his work. 2) Results of the role of the carpet craft industry from abaca banana fiber CV. The natural way to improve people's welfare is to overcome unemployment by opening up employment opportunities, increasing economic income, meeting living needs, and improving human resource skills